Hydroxychloroquine improves dry eye symptoms of patients with primary Sjogren's syndrome - TOKER, AYŞE EBRU (SPRINGER HEIDELBERG, 2011)
The objective of the study is to investigate the effect of hydroxychloroquine (HCQ) on subjective and objective parameters of dry eye in patients with primary Sjogren's disease and to evaluate the association of tear fluid B-cell activating factor (BAFF) level with the response. Thirty-two patients with primary Sjogren's disease were enrolled in this prospective study. All patients included in the study completed at least a 48-month run-in period of using hydroxychloroquine. Patients were then instructed to drop the treatment for 3 months. Baseline and post cessation of treatment (baseline and 3 months) evaluations included, subjective symptom scoring, fluorescein and lissamine green staining, Schirmer's test, tear break-up time (BUT) and tear fluid BAFF assessments. Significant worsening was observed in, tear break up-time (TBUT) (7.9 +/- A 3.4 vs. 5.9 +/- A 2.9, P < 0.001) lissamine green of staining of the ocular surface (1.3 +/- A 0.9 vs. 1.8 +/- A 0.8, P < 0.01) and corneal fluorescein staining scores (2.2 +/- A 2.1 vs. 4.6 +/- A 3.3, P < 0.003) between on and off HCQ treatment, respectively. Similarly, gritty sensation and burning sensation were significantly changed at week 12 compared to baseline evaluation (1.18 +/- A 1.02 vs. 1.7 +/- A 1.05, P < 0.007 and 1.1 +/- A 1.0 vs. 1.6 +/- A 1.2, P < 0.0, respectively). Disease duration significantly correlated with baseline OSDI (r = 0.38, P < 0.04) and the average daily use of artificial tears (r = 0.36, P < 0.04). The mean BAFF levels were 0.8 +/- A 0.5 and 4.0 +/- A 0.7 ng/ml for baseline and week 12 evaluation, respectively (P < 0.0001). The results of this study suggest that HCQ may alleviate symptoms and signs of dry eye in pSS and decreases tear fluid BAFF levels.
Keywords: Sjogren's syndrome; Hydroxychloroquine; Xerophthalmia; BAFF; TEAR FLUID; EPITHELIAL-CELLS; B-CELLS; BAFF; AUTOANTIBODIES; DISEASE; CORNEAL; OVEREXPRESSION; CONJUNCTIVA; THERAPY